Phytochemical Constituents, Nutritional and Antibacterial Potentials of Selected Medicinal Plants (Allium sativum, Chromolaena odorata, and Talinum triangulare) - Adebisi Musefiu Tiamiyu; Reuben Chukwuma Okocha; Olayemi A Okunlade; Isaac Olufemi Olatoye; Olufemi Bolarinwa Adedeji (Majalah Obat Tradisional, 2023)
Alternate medicine practices using natural plant extract may be of great importance in combating public health challenges. Medicinal plants are the bases for the development of modern drugs; accepted to treat infectious diseases globally. This study investigated the phytochemical constituents, proximate composition, and antibacterial activity of Allium sativum (garlic), Chromolaena odorata (Siam weed), and Talinum triangulare (Waterleaf) due to their reported medicinal properties. The phytochemical constituents and proximate composition were analysed using standard protocols. Agar diffusion technique was used to evaluate the antibacterial activities of the plants. All three plants included innumerable quantities of phytochemicals such as alkaloids, tannins, phlobatannins, saponins, flavonoids, anthraquinones, steroids, phenol, and cardiac glycoside. Proximate analysis indicated that the moisture (9.88%), fiber (4.57%), crude fat (2.89%), crude protein (3.67%), ash (3.78%), and carbohydrate (75.21%) present in Allium sativum; moisture (9.26%), fiber (15.28%), crude fat (3.56%), crude protein (18.86%), ash (11.76%), and carbohydrate (41.28%) present in Chromolaena odorata; moisture (10.37%), fiber (16.43%), crude fat (2.23%), crude protein (11.88%), ash (13.29%), and carbohydrate (45.80%) present in Talinum triangulare. The crude extract of Chromolaena odorata had the highest zone of inhibition against Pseudomonas aeruginosa (12.5mm). These bioactive substances, such as phenol, alkaloids, flavonoids, saponins, and tannins, augment the therapeutic characteristics of these plants, making them a common component of traditional remedies. They may serve as primes to drug discovery and be integrated into the health care delivery system. The investigations proved these plants' medicinal potential and further demonstrated Chromolaena odorata and Talinum triangulare's nutritional potential. They are good sources of income for individuals and bioprospecting.